2019
DOI: 10.1016/j.jtho.2019.08.1593
|View full text |Cite
|
Sign up to set email alerts
|

P2.04-88 Surgical Outcomes of a Multicenter Phase II Trial of Neoadjuvant Atezolizumab in Resectable Stages IB-IIIB NSCLC: Update on LCMC3 Clinical Trial

Abstract: 2018 in Japan. Method: To investigate the feasibility of concurrent CRT for LA-NSCLC patients and efficacy of ICI treatment for the relapsed patients after CRT, we assessed consecutive LA-NSCLC patients treated with concurrent CRT between July 2013 and June 2018 (before durvalumab approval), retrospectively. Result: 108 eligible patients (81 males and 27 females with median age of 65 years old, including 7 patients with targeted mutations; 2 EGFR, 4 ALK and 1 ROS1) were analyzed. All patients received radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…(2019) 32 Lee et al. (2019) 21 IB–IIIB Atezolizumab (2 cycles) Day 40 ± 10 d after first dose of atezolizumab 90 (89%)/101 NR Surgery occurred outside 10-d protocol window (range: 2–43 d) in 10% (10 pts): TRAE (n = 2), surgeon availability (n = 2), other (n = 6) 11/101 (11%) (5/101 [5%; stage IIIA] had preoperative PD, 4/101 [4%] withdrew consent, 1/101 [1%] failed ECG, 1/101 [1%; stage IB] had involvement of pulmonary artery) 0% 5/101 (5%); these patients had stage IIIA or IIIB NCT02994576 PRINCEPS Besse et al. (2020) 12 I–IIIA Atezolizumab (1 cycle) 3 wk after atezolizumab and within <15 d of that window 30 (100%)/30 Median, 24 d None delayed >15 d 0% 0% 0% NCT02259621 CheckMate 159 Bott et al.…”
Section: Delays To Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…(2019) 32 Lee et al. (2019) 21 IB–IIIB Atezolizumab (2 cycles) Day 40 ± 10 d after first dose of atezolizumab 90 (89%)/101 NR Surgery occurred outside 10-d protocol window (range: 2–43 d) in 10% (10 pts): TRAE (n = 2), surgeon availability (n = 2), other (n = 6) 11/101 (11%) (5/101 [5%; stage IIIA] had preoperative PD, 4/101 [4%] withdrew consent, 1/101 [1%] failed ECG, 1/101 [1%; stage IB] had involvement of pulmonary artery) 0% 5/101 (5%); these patients had stage IIIA or IIIB NCT02994576 PRINCEPS Besse et al. (2020) 12 I–IIIA Atezolizumab (1 cycle) 3 wk after atezolizumab and within <15 d of that window 30 (100%)/30 Median, 24 d None delayed >15 d 0% 0% 0% NCT02259621 CheckMate 159 Bott et al.…”
Section: Delays To Surgerymentioning
confidence: 99%
“…For example, in the LCMC3 study of atezolizumab monotherapy, 2% of patients had their surgery delayed by AESIs: hypothyroidism (10 d) and pneumonitis (43 d). 21 In the TOP1201 study of neoadjuvant ipilimumab plus CT, 15% of patients had delays of 28 and 35 days, respectively, owing to ipilimumab-related diarrhea 22 ( Table 2 ), described as an irAE ( Table 3 ). By contrast, in the ChiCTR-OIC-17013726 study of neoadjuvant sintilimab, 5% of patients had delayed surgery owing to TRAEs (grade 2 alanine aminotransferase and aspartate aminotransferase elevations and grade 1 hypothyroidism) but no distinction from other TRAEs was made, 23 nor was any distinction made in the MK3475-223 study of neoadjuvant pembrolizumab, in which 7% of patients had a delay owing to grade 3 treatment-related myositis.…”
Section: Delays To Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a number of phase III clinical studies of neoadjuvant immunotherapy including CheckMate 816, Keynote-671, and IMPOWER030 among others are under way. Although the potential benefit of neoadjuvant immunotherapy was seen in the early phase I/II clinical studies, some immunotherapy related concerns were also noticed (4,(11)(12)(13). For example, Figure 5 Treatment timeline of our case.…”
Section: Discussionmentioning
confidence: 88%
“…These studies have reported MPRs of 19%-45% for neoadjuvant ICI monotherapy, 33% for combination ICI therapy, and as high as 85% for ICI combined with chemotherapy. Phase I/II clinical studies have also demonstrated the beneficial potential of perioperative immunotherapy, although several studies 6,[14][15][16] reported AEs resulting in delayed surgery, altered surgery mode, reduced operative benefit, prolonged hospital stay, and increased economic burden on patients. Moreover, the incidence of perioperative complications and mortality was increased for patients with severe AEs.…”
Section: Introductionmentioning
confidence: 99%